The Fragmented Malay Self: A Critical Study Of Selected Works by Dina Zaman, Karim Raslan and Huzir Sulaiman - Zainal Abidin, DZeelfa (2004)
This thesis seeks to analyse the portrayal of the characters in the works of three Malaysian writers- Dina Zaman, Karim Raslan and Huzir Sulaiman. The characters of the selected works are of the Malay ethnicity and this study aims to look at their sense of self and ethnic identity of being Malay. The self is not whole and united. It is fkgmented and conflicting in nature. A Malay-self is generally defined as "a person who professes the religion of Islam, habitually speaks the Malay language, conforms to Malay customs" by the Federal Constitution in Article 160. This is the basis for the Malay ethnic identity in the country. The characters in the selected works used in this research may or may not conform to the aforementioned definition and bear with them fragmentalised identities of their selves. Therefore, in light of the fragmented self and ethnic identity, the portrayal of the Malay-selves in the selected writings will be examined.